Recensions / Book Reviews: Leonidas T. Chrysanthopoulos, Caucasus Chronicles: Nation-building and Diplomacy in Armenia, 1993- 1994, Princeton and London: Gomidas Institute Books, 2002, 180 pages. - Philippoussis, Yannis (Études helléniques / Hellenic Studies, 2002)
Leonidas T. Chrysanthopoulos, Caucasus Chronicles: Nation-building and Diplomacy in Armenia, 1993-1994, Princeton and London: Gomidas Institute Books, 2002, 180 pages.